2021
DOI: 10.21037/qims-20-1274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction models of fractional flow reserve: an exploration of the current evidence and appraisal of model performance

Abstract: Background: Invasive fractional flow reserve (FFR) is a standard indicator of coronary stenoses' hemodynamic severity. Clinical prediction models (CPMs) may help differentiate ischemic from nonischemic lesions without using a pressure wire but by integrating related variables. This approach differs from that of physics-based models. However, it is not yet known which CPMs are the most reliable at detecting hemodynamic significance.Methods: A systematic review was performed of relevant publications that develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Coronary artery calcification was not associated with the pressure gradient before and after the administration of adenosine [ 22 ]. Lesion length (82%), QCA-DS (64%), and minimum lumen diameter (55%) were reported as the most frequently used variables in the 11 clinical prediction models for FFR whereas calcification was only used in one of them (9%) [ 23 ]. Velangi et al [ 24 ] also found that only lesion length and low-attenuation plaque were significant independent predictors of ischemia detected by FFR although spotty calcification was predictive of abnormal FFR on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcification was not associated with the pressure gradient before and after the administration of adenosine [ 22 ]. Lesion length (82%), QCA-DS (64%), and minimum lumen diameter (55%) were reported as the most frequently used variables in the 11 clinical prediction models for FFR whereas calcification was only used in one of them (9%) [ 23 ]. Velangi et al [ 24 ] also found that only lesion length and low-attenuation plaque were significant independent predictors of ischemia detected by FFR although spotty calcification was predictive of abnormal FFR on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional flow reserve (FFR) is the "gold standard" for evaluating the physiological function of coronary arteries. FFR-guided percutaneous coronary intervention (PCI) can improve the prognosis while reducing the medical costs of patients (2). However, the use of FFR in China is limited due to various factors, including its low penetration rate, invasive nature, high cost, lengthy operation time, lack of a standard fee structure, and inadequate medical insurance coverage (3,4).…”
Section: Introductionmentioning
confidence: 99%